2020
DOI: 10.1111/jocd.13485
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression of IL‐17A and FOXP3 in acne vulgaris patients

Abstract: Acne vulgaris presently assumed as a chronic inflammatory disorder of the pilosebaceous component. 1 It is considered the most prevalent worldwide disease as it affects, in the developed countries, 85% of adolescents and about 9.4% of the world's population. 2 AV is a result of interplay of androgen-induced augmented sebum secretion, follicular hyperkeratinisation, loss of skin microbial diversity (colonization by propionibacterium acnes, P. acne) and inflammatory reactions plus altered adaptive immune reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…It has been illustrated that the number of mast cells was observed to be increased in adjacent areas to the sebaceous glands in the acne lesion (45). Substance P (SP), a kind of neuropeptide associated with stress-induced acne, could stimulate mast cells degranulation and macrophage in ltration (15) as well as stimulate the release of a series of pro-in ammatory cytokines such as IL-6, IL-1, and TNF-α(46)from sebocytes. Hao Jiang et.al found that in acne lesions, a massive uptake of oxidized lipid could lead to the generation of neutrophils (foam cells) and lipid-loaded macrophages (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been illustrated that the number of mast cells was observed to be increased in adjacent areas to the sebaceous glands in the acne lesion (45). Substance P (SP), a kind of neuropeptide associated with stress-induced acne, could stimulate mast cells degranulation and macrophage in ltration (15) as well as stimulate the release of a series of pro-in ammatory cytokines such as IL-6, IL-1, and TNF-α(46)from sebocytes. Hao Jiang et.al found that in acne lesions, a massive uptake of oxidized lipid could lead to the generation of neutrophils (foam cells) and lipid-loaded macrophages (47).…”
Section: Discussionmentioning
confidence: 99%
“…The in ltration of IL-17 producing cells and elevated forkhead box P3 (FOXP3) expression have been found in acne lesions indicating a loss of FOXP + cells function de ciency (13,14). The impact of psychological stress on acne has been mentioned and the release of substance P from skin-expressed neurons under psychological stress could in uence mast cell activities (15). The in ammatory response to C. acnes promotes the development of large numbers of neutrophils and T lymphocytes (16) around acne lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Identified by the transcription factor FOXP3, these cells were detected in acne-affected individuals in their epidermis and in papillary dermis. Nevertheless, these cells do not appear to be associated with IL-17-producing cells, which might suggest a deficit in Treg function in acne vulgaris to control inflammatory events ( Farag et al, 2020 ).…”
Section: Inflammatory Response In Acnementioning
confidence: 99%
“…Proinflammatory IL-17-generating cells and anti-inflammatory FOXP3 + Treg cells are the main factors for CD4 + T cells to play a crucial role in inflammatory diseases. In acne vulgaris, the expression levels of IL-17 and FOXP3 are increased in epidermal keratinocytes and lymphocytes (58). Cutibacterium acnes can induce the activation of IL-17, with one study finding that the expression of serum IL-17 was increased in patients with acne vulgaris scarring compared to those without (59).…”
Section: Progress Of Research In Immunological Pathogenesis In Acne V...mentioning
confidence: 99%
“…IL-17A plays an important role in acne vulgaris in a paracrine manner involving interaction between dermal lymphocytes and epidermal keratinocytes (60). IL-17, TNF-α, and IL-1 play synergistic roles in acne vulgaris by inducing the production of several metalloproteinases (58). Platelets may play a role in adaptive immunity in acne vulgaris by up-regulating lymphocytes (61).…”
Section: Progress Of Research In Immunological Pathogenesis In Acne V...mentioning
confidence: 99%